Contribution to the current list of Nitzschia species (Bacillariophyceae) in Malaysia - Pau, Suriyanti Su Nyun; Nasir, Dzulhelmi Muhammad; Usup, Gires (Universitas Malikussaleh, 2021)
Current occurrence of Nitzschia Hassall from marine and freshwater environment in Malaysia is compiled from current and previously published materials. Phytoplankton was collected using a 20 µm plankton net from waterfronts of Peninsular Malaysia and Borneo. Some Nitzschia cells were successfully isolated and established into clonal cultures. For morphology observation, organic matters of the net samples and cultures were oxidized and removed through acid treatment. Cleaned specimens were observed using light and electron microscopes. The morphology of the Nitzschia cells was described and micrographs are included. In addition to current field sampling, Nitzschia spp. records and distributions in Malaysia had also been compiled from secondary data. Sources of references whereby the Nitzschia species were listed in this article were cited accordingly. This article compiles a total of 11 Nitzschia spp. found in Malaysia including a few revisions and new records. This article could serve as an important reference for Nitzschia taxonomic and distributional study particularly in tropical region.Keywords: distribution, morphology, taxonomy, tropical